Aloha :)
$$I_a=\int\frac{1}{(x+1)\ln(x+1)}\,dx=\int\frac{1}{\ln(x+1)}\cdot\frac{1}{1+x}\,dx$$Substituiere:\(\quad u\coloneqq\ln(x+1)\;\text{mit}\;\frac{du}{dx}=\frac{1}{x+1}\)$$\phantom{I_a}=\int\frac{1}{u}\cdot\frac{du}{dx}\,dx=\int\frac1u\,du=\ln|u|+\text{const}=\ln|\ln(x+1)|+\text{const}$$
$$I_b=\int\underbrace{e^{-2x}}_{=u'}\cdot\underbrace{(x-4)}_{=v}\,dx=\underbrace{\frac{e^{-2x}}{-2}}_{=u}\cdot\underbrace{(x-4)}_{=v}-\int\underbrace{\frac{e^{-2x}}{-2}}_{=u}\cdot\underbrace{1}_{=v'}\,dx$$$$\phantom{I_b}=-\frac{e^{-2x}}{2}(x-4)+\frac12\int e^{-2x}\,dx=\pink{-\frac{e^{-2x}}{2}}(x-4)+\frac12\cdot\pink{\frac{e^{-2x}}{-2}}+\text{const}$$$$\phantom{I_b}=\pink{-\frac{e^{-2x}}{2}}\left(x-4+\frac12\right)+\text{const}=-\frac{e^{-2x}}{4}(2x-7)+\text{const}$$